The Effect Of Liquid Organic Fertilizer And Media Combination Of Organic To Plant Red Chili Pepper (Capsicum annum L.) - M Abror; Miftahul Huda Alhaq (Nabatia, 2017)
This study aims to describe the effect of a combination of liquid organic fertilizer and organic media on the growth and yield of red chili (Capsicum annum L.). The research was conducted at the Greenhouse, Faculty of Agriculture, University of Muhammadiyah Sidoarjo. The research was arranged in a factorial with a completely randomized design (CRD) consisting of two treatment factors. The first factor is three types of liquid organic fertilizer for Lamena Leaf Plants, Fish Manure Liquid Organic Fertilizer, Liquid Organic Fertilizer Combination of Vegetable Leaves and Fish Manure with a concentration of 15 ml / liter. The second factor consists of four types, namely soil and cow dung, goat manure and soil, soil and horse manure. Data obtained in Analysis Of Variance (Annova) and continued with HSD 5%. The variables observed were plant height, number of leaves, number of branches, wet weight, dry weight, number of fruit plants and fruit weight. The results showed that the combination of fish waste liquid organic fertilizer and the combination of organic media showed the interaction of the portion of the observation variable, namely the high number of fruit plants and dry weight. On (a combination of animal liquid organic fertilizer and soil organic media) showed the highest treatment dose and (liquid organic fertilizer a combination of animal and soil organic media and goat manure) showed the lowest treatment on the impact of plants. In a single treatment, liquid organic fertilizer does not have a significant effect on all observation variables.